Antioxidant, Antibacterial, Cytotoxic, and Anticancer Potential of Belulang Grass (Eleusine indica) - Vanda Selvana Kamu; Max Revolta John Runtuwene; Jetlee Merentek; Harry Steven Julius Koleangan; Maureen Kumaunang (Jurnal Ilmiah Sains, 2025)
A study was conducted to determine the antioxidant, antibacterial, cytotoxic, and anticancer activities of the belulang grass plant (Eleusine indica). Antioxidant activity was assessed using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity method. Antibacterial activity was determined using the disk diffusion method, cytotoxicity was determined using the Brine Shrimp Lethality Test (BSLT), and anticancer activity was evaluated using the MTS assay. The results showed that the antioxidant activity of the extracts and solvent fractions of Eleusine indica had the highest average value for the n-hexane fraction (FNH) at 35.0%, ethyl acetate fraction (FEA) at 56.4%, aqueous fraction (FA) at 30.3%, and methanol extract (EM) at 32.5%. Among these, the highest value was obtained in FEA, while the lowest was obtained in FA. Based on the cytotoxicity test with the BSLT method, the ethyl acetate fraction had an LC50 value of 7.384 ppm, categorizing it as highly toxic. However, in cytotoxicity testing with HeLa cells, the IC50 value for the ethyl acetate fraction was 223.70 ppm, indicating that the ethyl acetate fraction was less active against HeLa cervical cancer cells. Keywords: Eleusine indica; belulang grass; cytotoxic; HeLa cells